2022
DOI: 10.1108/ejm-04-2020-0308
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the threat of COVID-19 on visiting intentions as influenced by different destination logos

Abstract: Purpose This research aims to examine the role of perceived threat (i.e. COVID-19) on people’s preferences for destination logo designs. In addition, it investigates the influence of childhood socioeconomic status (SES) and sensation seeking on the aforementioned effect. Design/methodology/approach Five experiments are used. Studies 1 A and 1B examine the impact of the threat of COVID-19 on visiting intentions as influenced by different destination logos. Study 2 replicates the previous studies and tests for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 104 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…First, we extend the growing literature on how disease threat influences consumer behavior. Although the existing literature offers insights into how consumers respond to a disease threat, for example, preference for uncrowded travel and hospitality options (Park et al, 2021), destination logo design (Kim et al, 2022), nostalgic products (Barauskaitė et al, 2022), and pattern seeking in sequential choices (Park, Kim, Lee, et al, 2022), our study, especially Studies 1 and 4, enriches this stream of literature by uncovering a novel downstream consequence of disease threat (i.e., decreased preference for densely displayed products) using lab and field data. Moreover, Studies 2 and 3, respectively, showed that the disease‐density effect diminishes when diseases are not infectious or when disinfection products are displayed.…”
Section: Discussionmentioning
confidence: 99%
“…First, we extend the growing literature on how disease threat influences consumer behavior. Although the existing literature offers insights into how consumers respond to a disease threat, for example, preference for uncrowded travel and hospitality options (Park et al, 2021), destination logo design (Kim et al, 2022), nostalgic products (Barauskaitė et al, 2022), and pattern seeking in sequential choices (Park, Kim, Lee, et al, 2022), our study, especially Studies 1 and 4, enriches this stream of literature by uncovering a novel downstream consequence of disease threat (i.e., decreased preference for densely displayed products) using lab and field data. Moreover, Studies 2 and 3, respectively, showed that the disease‐density effect diminishes when diseases are not infectious or when disinfection products are displayed.…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides support that perceived risk and psychological resilience are explanatory factors for well-being and should be key mediators for the current study. Related to the travel aspect of the travel–well-being relationship, Kim et al (2022) show that perceived risk of COVID-19 mediates the relationship between simple destination logo designs and higher visiting intentions. Thus, it appears that when travel is considered, perceived risk could play a mediating role.…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…Since organizations have adapted their marketing practices to attract consumers in the new normal due to COVID-19 induced changes in the consumption patterns (Carracedo et al, 2021), place branding strategies also need to be revamped. As such, researchers (Cambra-Fierro et al, 2022; Kim et al, 2022) have examined the impact of branding strategies, such as destination brands’ logo design and communication on tourists’ preference for a destination in the post-pandemic world. The place branding literature suggests that branding strategies, such as building destination brand personality (Hultman et al, 2017) and destination brand equity (Bose et al, 2016), are key to drive tourists’ preference for a destination.…”
Section: Future Research Directionsmentioning
confidence: 99%